2007
DOI: 10.1037/0278-6133.26.3.369
|View full text |Cite
|
Sign up to set email alerts
|

Using motivational interviewing as a supplement to obesity treatment: A stepped-care approach.

Abstract: For individuals experiencing weight loss difficulties during a BWLP, MI may have considerable promise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
144
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(158 citation statements)
references
References 18 publications
9
144
0
5
Order By: Relevance
“…Motivational interviewing is recognized as an important approach to behavior change in multiple health contexts (Armstrong et al, 2011;Befort et al, 2008;Bennett et al, 2007;Carels et al, 2007;Hardcastle et al, 2008;Heckman et al, 2010;Jenson et al, 2011;Lai et al, 2010;O'Halloran et al, 2014). MI has also been recognised as a complex approach to interventions comprising multiple techniques (Michie et al, 2013;Miller & Rollnick, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Motivational interviewing is recognized as an important approach to behavior change in multiple health contexts (Armstrong et al, 2011;Befort et al, 2008;Bennett et al, 2007;Carels et al, 2007;Hardcastle et al, 2008;Heckman et al, 2010;Jenson et al, 2011;Lai et al, 2010;O'Halloran et al, 2014). MI has also been recognised as a complex approach to interventions comprising multiple techniques (Michie et al, 2013;Miller & Rollnick, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Motivational interviewing (MI) has been shown to be a promising approach for promoting health behavior change in a number of contexts including substance abuse (Jenson et al, 2011), quitting smoking (Heckman, Egleston, & Hofmann, 2010;Lai, Cahill, Qin, & Tang, 2010), physical activity promotion (Bennett, Lyons, Winters-Stone, Nail, & Scherer, 2007;Carels, Darby, Cacciapaglia, Konrad Coit, & Harper, 2007;Hardcastle, Blake, & Hagger, 2012;Hardcastle, Taylor, Bailey, & Castle, 2008;O'Halloran et al, 2014), and dietary change (Armstrong et al, 2011;Befort et al, 2008). MI can be considered a complex intervention comprising multiple techniques to promote behavior-change.…”
Section: Motivational Interviewingmentioning
confidence: 99%
“…Finally, Carels et al (2007) evaluated the use of MI as part of a stepped-care approach to BWL treatment. Fifty-five overweight participants were randomized to receive group treatment only (24 weeks of LEARN), or group treatment plus the option of weekly individual MI sessions, if they failed to meet weight loss goals.…”
Section: Motivational Interviewing In Behavioral Weight Loss Treatmentmentioning
confidence: 99%
“…Carels et al 3 similarly found greater program adherence and weight losses in their study of MI delivered in a stepped-care manner to overweight individuals (who may or may not have had type 2 diabetes, although insulindependent individuals were excluded). Participants who were randomized to receive MI were offered sessions only if they encountered a weight loss plateau.…”
Section: Incorporating Motivational Interviewing Into Counseling For mentioning
confidence: 92%